Global Post-Fordism and Concepts of the State - Bonanno, Alessandro; H. Friedland, William; Llambi, Luis; Marsden, Terry; Belo Moreira, Manuel; Schaeffer, Robert (The International Journal of Sociology of Agriculture and Food, 2021)
Following a review of the literature on the State and some of the basic features of global post-Fordism, it is maintained that global post-Fordism can be synthesized through a set of four dialectical relationships: deregulation/re-regulation, fragmentation/coordination, mobility/embeddedness and empowerment/disempowerment. Moreover, it is argued that: 1) the State in global post-Fordism cannot be thought of exclusively in national terms; 2) its re-conceptualization must entail a transnational dimension; 3) the State cannot be conceptualized exclusively in terms of formal public appearances, agents and agencies; and 4) non-public apparatuses, agents and agencies must be included in the analysis.